2017
DOI: 10.1016/j.jacep.2016.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Cardiac Arrhythmias in Patients With Anthracycline-Related Cardiomyopathy

Abstract: This study indicates that the burden of arrhythmia in patients with anthracycline-related cardiomyopathy is not different from cancer and non-cancer patients with IHD-related LVD or DCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 34 publications
2
22
0
2
Order By: Relevance
“…Of note, none of the AICM patients died suddenly, suggesting anyway that less frequent ICD implantation did not negatively affect their outcome: this finding is in line with recent published literature and corroborates the recent findings by Mazur et al . about the similar burden of arrhythmias in AICM patients with CRT/ICD, compared with both cancer and non‐cancer patients suffering from ischaemic LV dysfunction or IDCM: interestingly, in this recent report, clinical outcomes, including device therapy, OHT, and overall mortality, did not differ between groups, as previously described . A recent retrospective study also showed comparable outcome of VAD and/or OHT in 17 patients with end‐stage AICM vs. 51 patients with IDCM matched for co‐morbidities and severity of LV dysfunction, although a greater proportion of patients in the AICM group developed recurrent or new primary cancer …”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Of note, none of the AICM patients died suddenly, suggesting anyway that less frequent ICD implantation did not negatively affect their outcome: this finding is in line with recent published literature and corroborates the recent findings by Mazur et al . about the similar burden of arrhythmias in AICM patients with CRT/ICD, compared with both cancer and non‐cancer patients suffering from ischaemic LV dysfunction or IDCM: interestingly, in this recent report, clinical outcomes, including device therapy, OHT, and overall mortality, did not differ between groups, as previously described . A recent retrospective study also showed comparable outcome of VAD and/or OHT in 17 patients with end‐stage AICM vs. 51 patients with IDCM matched for co‐morbidities and severity of LV dysfunction, although a greater proportion of patients in the AICM group developed recurrent or new primary cancer …”
Section: Discussionsupporting
confidence: 77%
“…17 years ago (<50%) and was substantially equivalent to the 86.5% rate recently reported by Mazur et al . in a small, but well characterized cohort of long‐term adult cancer survivors with AICM, followed for up to 8.5 years after CRT/ICD implantation . This finding is even more remarkable considering that a significant proportion of our AICM patients received thoracic radiotherapy and/or additional anticancer chemotherapy prior to the most recent anthracycline exposure, and that use of the less toxic liposomal anthracyclines was limited.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Despite the limited sample size, these data are consistent with recently published results demonstrating the burden of arrhythmias in patients with CIC is similar to other forms of cardiomyopathy. 12 …”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies have been published evaluating the frequency of arrhythmias or ICD therapies and outcomes in patients with chemotherapy-induced cardiomyopathy (CIC). 12 The purpose of our study was to examine the prevalence of atrial and ventricular arrhythmias in patients with CIC treated with ICDs compared with a matched population of patients with either ischaemic cardiomyopathy (ICMO) or other types of non-ischaemic cardiomyopathy (NICMO).…”
Section: Introductionmentioning
confidence: 99%